Softening of Circulating Water in the Cooling System of Mine Compressor Devices - Ergashovich, Yuldoshov Husniddin; qizi, Mirzayeva Ma’mura Ubaydulla (Researchparks Publishing, 2023)
Today, a number of significant shortcomings of the cooling system have been identified in the use of mining compressor devices all over the world, which are caused by the specific features of their working principle. Thus, not cooling the air in reciprocating compressors every 5-6℃ increases the electricity consumption for air compression by 1%, and the efficiency decreases by 8-10%, causing a significant economic loss in the production of compressed air. In this regard, there is a need to study the effect of the cooling quality of the compressed air on the efficiency of the compressor device, to improve the cooling system, to develop a device for softening the supply water, to develop the scientific basis for increasing the efficiency of mining compressor devices.